An Application of ELECTRE Tri to Support Innovation. Issue 1 (20th December 2013) - Norese, Maria Franca; Carbone, Vincenzo; Dias, Luis Cândido; Mousseau, Vincent
ABSTRACT In relation to the economic crisis, the airports were pressed from their national civil aviation authorities and from the market to lower their costs and improve their capability in organizing the supply of public facilities. Some airports reacted to this situation improving their efficiency in invoicing and collecting user charges. An enterprise that supplies different services to the Italian Aviation Authority and to several Italian companies who are airport concessionaires decided to analyse the Italian airport revenues from off‐flight services, in order to compare their different results and help them improve their product offerings and identify new products' value drivers. To meet this requirement, an outranking method, ELECTRE Tri, was used to evaluate the marginal and overall activation of each Italian airport in reacting to the crisis and making profit by organizing public facilities and services that are different from the classic air navigation services on the ground. The choice of the method and the adopted procedure were motivated by the difficulties in reliable data acquisition, comparison of different and almost incomparable situations and preference elicitation, without the involvement of the actual decision makers and, in relation to a sequence of model versions, different in terms of problem structuring and parameters definition. A collaborative procedure of model structuring and incremental result analysis and several ELECTRE Tri applications, assigning each airport to a specific category, were oriented to the generation of a 'robust' model and a clear result, to read and synthesize all the information elements, understand the situation and acquire a shared vision of the problem, orient the process of information acquisition and support the definition of some improving actions. Copyright © 2013 John Wiley & Sons, Ltd.